Daniel on solid ground - Ferch, Arthur J. (Review and Herald Publ. Assoc., 1988)
Many biblical scholars believe Daniel was composed by an unknown second-century author who posed as the sixth-century prophet Daniel. He pretended to have transmitted genuinely inspired predictions about the future, which in reality were no more than historical narratives. This is known as Maccabean thesis. Its advocates are intelligent and biblically literate. But if their thesis is right, God is discredited as the great director of world history. Can the Adventist understanding of Daniel be maintained withour compromising intellectual integrity? Yes, it can! And in "Daniel on Solid Ground," Arthur J. Ferch sets out to prove it. "Daniel on Solid Ground" will help you construct a reasonable witness for others and a deeper confidence in God's purposeful control of history. - 1 Text and Canon. 2 Authorship and Unity. 3 The Date of Daniel. 4 The Maccabean Period; Daniel and Pseudonymity. 5 Daniel and Apocalyptic. 6 The Book of Daniel and Historicism